Causes of an elevated international normalized ratio in the intensive care unit and the implications for plasma transfusion. Issue 10 (22nd July 2021) - Cheves, Jared W.; DeMarinis, Sandra; Sorin, Claudia; Carino, Gerardo; Sweeney, Joseph D.
Abstract: Background: The presence of an elevated international normalized ratio (INR) is common in patients in the intensive care unit (ICU), but the cause rarely determined. These patients are at risk to receive prophylactic plasma prior to invasive procedures. Study design and methods: Samples from patients with an INR of 1.5 or greater were frozen and subsequently thawed and assayed for procoagulant and anticoagulant clotting factors and anti‐Xa to determine the likely cause of the INR. Samples showing a low FVII, FX, PC, and PS were categorized as a vitamin K deficiency pattern. Samples showing a low FV, low or normal fibrinogen, and high FVIII were categorized as a liver disease pattern. Samples showing an anti‐Xa >0.01 IU/ml were assayed for anti‐Xa DOACs. Samples which could not be categorized were grouped as equivocal. Results: A total of 48 samples were obtained over a 6‐month period. Nineteen showed a Vitamin K deficiency pattern, 17 a liver disease pattern, 7 showed an anti‐Xa DOAC and 5 were equivocal. High FVIII and D‐dimers and reduced levels of the anticoagulant proteins were present in the majority of the samples. FVII levels correlated inversely with the INR ( r  = −0. 81), as did FX ( r  = −0.67) but not FV ( r  = −0.04) nor fibrinogen ( r  = −0.15). Conclusion: Transfusion of plasma to reverse an elevated INR in the ICU should be discouraged since such a practice is either avoidable by the use of vitamin K or inappropriate in the case of liver disease or an anti‐Xa DOAC.